Learn Office 2016 for Mac - Hart-Davis, Guy (Apress : Imprint: Apress, 2016)
In this update to his excellent first edition, Guy Hart-Davis provides a practical, hands-on approach to using Office 2016 applications to create and edit documents and get work done efficiently. You'll learn how to customize Office, design, create, and share documents, manipulate data in a spreadsheet, and create lively presentations. You'll also discover how to organize your email, contacts, and tasks with the new Outlook for Mac. Conveying information quickly and concisely, this book takes you from beginner or intermediate to an experienced and confident user. Rather than cover every seldom-used feature, the book covers real-world usage, putting emphasis on practical tasks and troubleshooting common problems, such as sharing documents with Windows users and older versions of Office. If you need to learn to use Word, Excel, PowerPoint, and Outlook to get everyday tasks done, at work or at home, you will benefit from this book's focused approach and detailed advice - add it to your library today. .